Resin trapper - XU GUIQIAN; LU SHAOFEI; WU XUEZHONG; ZHANG QIANG; LI XIAOFEI (2017)
The utility model relates to a filter equipment field, concretely relates to a to resin trapper. Which comprises a housin, the casing outside is provided with the shell, be provided with the iron core between shell and the casing, be provided with the winding coil in the iron core, the shell both sides are provided with the end cover, the casing both ends are provided with the closing cap, a left side be provided with on the side sealing cover with the inside communicating blow off pipe of casing, be provided with the blowoff valve on the blow off pipe, the right side be provided with on the side sealing cover with the inside communicating feed liquor pipe of casing, shell right side on the casing be provided with with the inside drain pipe that communicates with each other of casing, be provided with filter equipment in the casing, still be provided with belt cleaning device in the filter equipment. The utility model relates to a, simple structure, convenient operation, characteristics such as no secondary p